The Use of Technology in Learning Arabic Langugage in Higher Education: an Overview - Haryono, Pauzan; Widiatmoko, Bambang (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
This paper contains an overview of learning Arabic in universities in the digital era. The points discussed are the use of technology in learning Arabic, the problem of learning methods and the assessment of learning outcomes. Technology of information is improving more and more sophisticated in line with the developing era. Smart learning is augmented with digital, context-aware, and adaptable technologies to encourage students to learn better and faster. To ensure that digital learning is successful and that implementation is efficient, it is critical that the dimensions of digital learning are arranged correctly. In this context, Arabic must be understood as an important part of the component in the planned effort to form an Islamic education. The existence of Arabic which in the understanding of education science is a tool for text investigation should be placed in the right position. Key words: Arabic, digital era, technology, learning methods